2010
DOI: 10.1080/02643294.2010.504580
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and interpretation of serial position data

Abstract: The representation of serial position in sequences is an important topic in a variety of cognitive areas including the domains of language, memory and motor control. In the neuropsychological literature, serial position data have often been normalised across different lengths, and an improved procedure for this has recently been reported by Mactynger and Shallice (2009).Effects of length and a U-shaped normalised serial position curve have been criteria for identifying working memory deficits. We present simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…middle or at the end of words are produced less accurately than at the beginning. Middle phonemes are more susceptible to interference from flanking phonemes (a U-shaped serial position curve) and non-initial phonemes have more chance to decay while the beginning of the word is being produced (a linearly decreasing curve; Glasspool et al, 2006;Olson et al, 2010;Romani et al, 2011b;Ward & Romani, 1998).…”
Section: Output Buffermentioning
confidence: 99%
See 2 more Smart Citations
“…middle or at the end of words are produced less accurately than at the beginning. Middle phonemes are more susceptible to interference from flanking phonemes (a U-shaped serial position curve) and non-initial phonemes have more chance to decay while the beginning of the word is being produced (a linearly decreasing curve; Glasspool et al, 2006;Olson et al, 2010;Romani et al, 2011b;Ward & Romani, 1998).…”
Section: Output Buffermentioning
confidence: 99%
“…Considering the rate of errors per phoneme and effects of word position is more informative. A buffer impairment predicts that error rates per phoneme will increase at all positions in longer words because all phonemes will deteriorate faster/be more susceptible to interference when more of them need to be stored (a disproportionate length effect, see Olson et al, 2010;Romani et al, 2011b). A buffer impairment may also predict linear positional effects since phonemes at the end of the word may have more chance to decay (Glasspool et al, 2006;Schiller et al, 2001;Ward & Romani, 1998).…”
Section: Effects Of Length Frequency and Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spelling accuracy has been demonstrated to vary as a function both of letter position within the syllable (Caramazza & Miceli, 1990) and morphemic status (Badecker, Hillis, & Caramazza, 1990); it is possible that SLC also varies as a function of these variables. Furthermore, Olson, Romani, and Caramazza (2010) suggested that measures of spelling accuracy as a function of letter position not be collapsed across word length for a single five-letter word accuracy function; instead, serial position effects should be investigated separately for different word lengths. However, because most studies reporting serial position effects include multisyllabic and -morphemic words and collapse across word length, Study 1b was conducted with a second, independently selected sample of 300 words that varied in word length and number of syllables and morphemes.…”
Section: Studymentioning
confidence: 99%
“…Spelling accuracy has been demonstrated to vary as a function both of letter position within the syllable (Caramazza & Miceli, 1990) and morphemic status (Badecker, Hillis, & Caramazza, 1990); it is possible that SLC also varies as a function of these variables. Furthermore, Olson, Romani, and Caramazza (2010) suggested that measures of spelling accuracy as a function of letter position not be collapsed across word length for a single five-letter word This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Study 1bmentioning
confidence: 99%